Inherent factors influence color variations in semimembranosus muscle of pigs. (March 2022) - Kirkpatrick, L.T.; Elgin, J.M.; Matarneh, S.K.; Wicks, J.C.; Daniels, R.P.; Yen, C.-N.; Bodmer, J.S.; Zumbaugh, M.D.; El-Kadi, S.W.; Silva, S.L.; Shi, T.H.; Gerrard, D.E.
Abstract: Variations in color, though a quality frustration, are common across the face of fresh and processed hams. Herein, we measured objective color across the semimembranosus (SM) muscle early postmortem and at 1440 min, then compared these differences against biochemical and metabolic characteristics responsible for pork quality development. Color ( L *, a *) differed ( P < 0.001) by zone and time but no interaction was evident. Lactate content and pH were highly correlated (R 2 = 0.92) at 30 min, but weakened (R 2 = 0.161412) by 1440 min. Lactate anaplerosis was not responsible for this lack of relationship. Glycolytic potential also differed across zone ( P < 0.001) and time ( P < 0.005). Differences in myoglobin expression and abundance, as well as mitochondrial DNA were notable ( P < 0.05) across zone. These data suggest inherent differences in SM muscle are key determinants of ham color variation, while postmortem metabolism may play a lesser role in driving this quality attribute.